The journey and glitches: a study on burnout and turnover syndrome among the nursing students in one of the nursing institutions of higher learning in Malaysia - Hamidah Hassan; Azila T,; Kelvin J M; NurulIzzatie M,; Khadijah N Roslih (Malaysian Journal of Medicine and Health Sciences, 2020)
Introduction: Burnout is a psychological syndrome experienced by an individual who is exposed to chronic stress. It is a state of emotional, physical, and mental exhaustion caused by excessive and prolonged stress. It is often associ¬ated with feelings of hopelessness and difficulties in dealing with work efficiency. As for students, going-through the process of learning is a complex stressful phenomenon causing of poor academic performance. The aim of the study was to explore causes of student nurses’ burnout followed by the intention to leave the program. Methods: This is a cross sectional study with total of 127 respondents selected based on Krejci Morgan (1970) sample size calculation from year 1 till year 3 nursing students. Maslach Burnout Inventory (2016) was used to measure the burnout-self test comprised of emotional exhaustion, depersonalization and personal achievement. Twenty-two (22 items) with 7- points scale measuring responses of “Never (0)” to “Every day (7).” For Part B, three open ended questions applied to the intention of leaving the program. Results: A total of 35% of students had the intention of leaving the nursing program and 54% occurred during the first and second year of the study. Stress and financial struggles triggered the intention of quitting the program and 68% felt the study was breaking them down. Conclusion: Pursuing the program despite of the glitches worth the fights, 99 % of respondents acknowledged that this program is worth their future profession. Through this program they learnt to handle their emotional problem calmly and look after patients and colleague’s problem effectively. Nursing is a field of knowledge of humanities, exclusively in the care of patients and Nursing has been able to educate and transform the society who were insufficient in lives into useful human beings.